Application of Bogoliubov-de Gennes equations to vortices in Hubbard superconductors. Issue 1753 (16th February 2015) - Wang, Chumin; Galván, César G.; Pérez, Luis A.
ABSTRACT: In this work, the formation of d -wave superconducting magnetic vortex is studied within the Bogoliubov-de Gennes formalism and the generalized Hubbard model, which leads to 2 N 2 coupled self-consistent equations for a supercell of N × N atoms. These equations determine the spatial variation of the superconducting gap as a function of the electron concentration and electron-electron interactions. The results show that the superconducting states induced by the correlated hopping (Δ t 3 ) are more sensitive to the presence of magnetic field than those induced by attractive nearest-neighbor interaction ( V ). Furthermore, we calculate the electronic specific heat as a function of the temperature for a given applied magnetic field, whose behavior has a qualitative agreement with experimental data.